Towards the trachoma elimination target in the Southern region of Ethiopia: How well is the SAFE strategy being implemented? - Asfaw, Mekuria; Zolfo, Maria; Negussu, Nebiyu; Tadesse, Fantahun; Tadele, Tafese; Sisay, Alemayehu; Seyum, Dawit; Gezmu, Tigist; Senkoro, Mbazi; Owiti, Philip; Adriaensen, Wim (The Journal of Infection in Developing Countries, 2020)
Introduction: Trachoma is one of the 20 neglected tropical diseases and a serious public health problem in Ethiopia. To reach the WHO elimination target by 2020, SAFE (Surgery, Antibiotics, Facial cleanliness, Environmental improvement) strategy has been implemented in the Southern Nations, Nationalities, and Peoples' Region (SNNPRs), Ethiopia. Scarce evidence exists regarding recent progress in achieving elimination of active trachoma (< 5%) and how well the SAFE strategy implemented. Methodology: A retrospective analysis of programmatic data in the period 2013-2018 was used. All trachoma endemic districts in SNNPR were included. Data collected from the Federal Ministry of Health on trachoma prevalence and SAFE strategy were analyzed. Results: Out of 134 endemic districts, only 35 had their planned impact survey, of which only 11 districts achieved the elimination target. Six districts reverted backwards from eliminated status to low (1) or moderate (5) level. The median prevalence of active trachoma in these 35 districts was 10% in 2017/18. In 2017, the mean antibiotic treatment coverage was 90%, but only 56% and 68% of districts implemented and reported on “F” and “E” components, respectively. In the high prevalence districts, only 10% delivered their planned five rounds of Zithromax® mass distribution. Conclusions: These data showed a lack in planned impact surveys with only a limited number of districts reached the WHO elimination threshold by 2018. Lack of attention on high prevalent districts, and recent reversal of trachoma eliminated districts to moderate or low prevalence levels argue for urgent and prioritized implementation of the SAFE strategy.